TOWARD QUEER POTENTIALITIES IN CHILD AND YOUTH CARE - Zaman, Bobbi Ali; Anderson-Nathe, Ben (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
Arguably, from the invention of adolescence at the beginning of the 20th century, developmental theory has served as the foundation of disciplinary study and professional practice with children and youth across the global West. Despite their founders’ assertions that development is culturally constructed, in educational and youth work practice contexts stage-based trajectories of normative human growth are largely erroneously accepted as ahistorical, apolitical, naturally occurring, and universally applicable. This paper presents critiques of developmentalism from historical, reconceptualist, and queer perspectives, calling into question the underlying principles of normalcy and abnormality that run through the developmental project. We pay particular attention to the potential of queer theory as an analytic to deconstruct developmentalism in the context of child and youth care, opening new possibilities for critical engagement with children and youth outside the context of development.